Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia - Mutmainnah, Andi; Sahade, Sahade; Idrus, Mukhammad (LPPM Universitas Bina Sarana Informatika, 2024)
This study aims to analyze the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange for 2018-2021 as measured by the Financial Ratios of Liquidity, Solvency, and Profitability. The variable of this research is Financial Performance. The population of this study is all transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021, totaling 31 companies. At the same time, the sample in this study was 6 transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) which were taken using the Purposive Sampling technique. Data collection was carried out using the documentation technique. The data analysis method used is qualitative, using financial ratio numbers. The results of this study indicate that Financial Performance as measured using (1) Liquidity ratios measured by the current ratio of the average company has increased, the highest and meets industry ratio standards is the company BIRD (242%). (2) Solvency ratio measured by debt to asset ratio on average has increased and decreased, the lowest and meets the industry ratio standard is BIRD company (22%). (3) Profitability ratio measured by net profit margin on average has increased and decreased, the highest and meets the industry ratio standard is BLTA company (30%).